CAPTURE THE CUSTOMER PRODUCT ATTRIBUTES PREFERENCES THAT INFLUENCE PURCHASE DECISION OF HAND SANITIZER DURING COVID-19 - Isna Nabilla Risafitri, Syafa
The use of hand sanitizers in every activity has become a routine habit during the COVID-19 pandemic, which opens up unlimited opportunities for small and medium enterprises (SMEs) by accommodating market demand for hand sanitizers. In Indonesia, many local SMEs have started producing their own brands. Researchers are helping manufacturers to explore customer product attribute preferences that influence purchase decisions of hand sanitizer by making new product developments and innovations during COVID-19. Conjoint analysis with the full-profile method was used to process 96 respondent data taken by stratified random sampling technique. There are five attributes used in this analysis, namely hand sanitizer quality, form, features, label, and packaging. The result of importance attribute from the highest values is the packaging (50%) with keychain bottle packaging (3.354), followed by quality (17%) with alcohol-based quality (0.957), then feature (12%) using natural scent feature (0.016), after that design (11%) with gel form (0.290), and the ending is the label (10%) with food-grade (0.143). Pearson’s R is 0.964 and Kendall’s tau is 0.783 that close to 1 and more than 0.5, indicating the high predictive accuracy. Both significance value (0.000) is less than 0.05, therefore the result shows high predictive accuracy.